Identifikasi pisang apuy sebagai kultivar unggul lokal kabupaten Majalengka - Acep Atma Wijaya (Fakultas Pertanian Universitas Yudharta Pasuruan, 2020)
The development of local cultivars is one of the activities that must be carried out in promoting their respective regions. Majalengka Regency is a developing Regency so there is a need for a commodity that characterizes the area. One commodity that can be developed for tourist attraction is the local Apuy Banana. The existence of Apuy bananas is increasingly pushed every year due to the presence of other superior banana cultivars, besides that the public's knowledge of the characteristics of Apuy's local bananas is still very diverse so it needs information about the characteristics of local Apuy bananas, so that the community can be uniform. The purpose of this study is to explore and identify local Apuy bananas as superior banana ingredients in Majalengka Regency. This study uses a census method of local Apuy cultivars, Pisang Raja Dakit and Pisang Raja Lemongrass. The results showed there was diversity between Apuy Local Bananas, Raja Dengkel Bananas and Raja Sereh Bananas in terms of Morphological characters. Based on the results of relationship analysis, the level of similarity between genotypes observed was in the range of 77 to 92,51.